PENGEMBANGAN COLLABORATIVE STRATEGIC READING DALAM PEMBELAJARAN MEMBACA PEMAHAMAN BAGI MURID DENGAN PROBLEMA BELAJAR MEMBACA DI SEKOLAH DASAR - Leliana Lianty (Perspektif Ilmu Pendidikan, 2016)
This study aims at producing the reading comprehention instructional strategies that can be implemented effectively in the instructional process for students with learning problems. The initial idea of this research was based on the fact that reading comprehention instructional strategies had not been seccessfully appied to improve studensâ€™ skills in reading comprehension. This research, conducted as from July 2012 through September 2013 at inclusive schools in Jakarta, applied the Research and Development (R&D) approach; consisting: (1) a preliminary stage, (2) development stage, and (3) testing and validation phase. The unit of analysis involves the classroom teacher who teaches Indonesian and students with learning problems in regular schools. Data collection applied the technique of observation, interviews, and test. The analysis of qualitative data with descriptive and quantitative data used non-parametric data analysis and Wilcoxson test. The results of the study show New Collaborative Strategic Reading affects the studentsâ€™ reading skill and their comprehension and improve instructional process. Therefore, the New Collaborative Strategic Reading can be used as an alternative strategy to reading comprehension.